Pengaruh Kesadaran Wajib Pajak, Kualitas Pelayanan dan Tingkat Penghasilan Terhadap Kepatuhan Pembayaran Pajak Bumi Bangunan - Irfan Donofan; Mayar Afriyenti (Jurnal Eksplorasi Akuntansi, 2021)
The purpose of this study was to determine the effect of taxpayer awareness, service quality and income rate on land and building tax payment compliance in Payakumbuh. Researchers distributed questionnaires to Land and Building Taxpayers registered with the Regional Finance Agency with a total sample of 100 samples using the convenience sampling method. The results showed that taxpayer awareness and service quality had a positive and significant effect on compliance with land and building tax payments with a significance value of 0.001 and 0.000 which were smaller than 0.05. Meanwhile, income rate has no effect on compliance with land and building tax payments with a significance value of 0.162 greater than 0.05. Recommendations for further research are expected to use other independent variables that are considered relevant to the research and use different sampling methods such as using the cluster sampling method.